Isavuconazole Breakthrough Disseminated *Fusarium fujikuroi* Infection in a Patient with Allogeneic Hematopoietic Stem Cell Transplant: Diagnostic and Therapeutic Challenges – A Case Report - Davide Bosetti; Chiara Bernardi; Geoffrey Merle; Laetitia C Dubouchet; Stavroula Masouridi-Levrat; Yves Chalandon; Dionysios Neofytos (healthbook TIMES. Oncology Hematology)
# Introduction